Electromechanical coupling coefficient of 1-3 connectivity barium titanate-portland cement composites - Rattiyakorn Rianyoi (2018)
This paper reports electromechanical properties of the newly developed 1-3 connectivity lead-free piezoelectric ceramic-Portland cement composites for smart structure applications. The composites were fabricated from barium titanate and Portland cement by the dice-and-fill method. The influences of barium titanate (BT) ceramic volume fractions from 30% to 70% on the electromechanical coupling coefficient of composite were investigated. The results indicate that the thickness electromechanical coupling coefficient (K t ) of the composite is influenced by the BT volume content. It was found that the thickness electromechanical coupling coefficient (K t ) could reach up to 21.52% when the composite with BT ceramic volume content was increased to 70%. © 2013 Copyright Taylor and Francis Group, LLC.